The Rowan Tree Church 18th Annual Report, Hallows 1999 ce-Hallows 2000 ce - Rowan Tree Church (Kirkland: WA: Rowan Tree Church, 2000)
The eighteenth annual report begins by reflecting on the past 20th anniversary of obtaining legal recognition. Rev. Paul Beyerl reflects on his own journey, moving from Minneapolis to Dallas, to Los Angeles before setting roots in Kirkland, Washington with his partner Rev. gerry Beyerl. Reflection of all Board Member’s experiences and the 16th Annual Retreat held at Yellowstone National Park is found throughout the report, as well as a section devoted to the event.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Beyerl, Paul V., Rev., 1945-; Rowan Tree Church--Appropriations and expenditures; Annual Retreat (16th : 2000 : Yellowstone National Park); Rowan Tree Church. Library; Hermit's Grove (Rowan Tree Church); Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Church work with prisoners; Prisoners--Religious life; Galadhrim Society of Unicorns; Prison Outreach Program; Mystery School of Lothloriën--Calendars; Annual reports